Spatial Reasoning Excellence: A Synergy of VanTassel-Baska's Integrated Curriculum Model and Talent Development - Alicia Cotabish; Debbie Dailey; Jason Trumble; Rachelle Miller (MDPI AG, 2024)
This manuscript explores the integration of spatial reasoning into K-12 education through the lens of Joyce VanTassel-Baska's Integrated Curriculum Model (ICM) and a talent development approach. It emphasizes the significance of nurturing spatial reasoning components-visualization, rotation, orientation, and perception-for academic success, problem-solving, and career prospects, especially for academically talented students. Through collaboration with talent development strategies, including mentorship and differentiated instruction, this approach provides a dynamic, real-world-focused learning experience. Inclusive and designed to engage the educational community, it aims to prepare students for complex global challenges, highlighting the transformative power of tailored education in developing versatile societal contributors.